Line Balancing Study and Analysis at a Tractor Assembly Line - Shakilla Nur Asimah Mat Hussin; Prof Madya. Dr Sh Salleh bin Sh Ahmad (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study addresses the extended cycle time of 165 minutes in the tractor assembly process at a manufacturing plant, resulting in a low weekly output of 14.5 units. The objectives were to analyze the existing assembly line, implement line balancing techniques, and evaluate the impact on productivity and efficiency. Data collection included task durations, worker assignments, and resource utilization, followed by a precedence diagram construction. Line balancing techniques, particularly the Largest Candidate Rule (LCR), were applied. Results showed a significant reduction in cycle time from 165 minutes to 111 minutes, leading to a 49% increase in theoretical maximum weekly output and a decrease in balance delay from 19.1% to 9.52%.